Rule learning by rats. - Murphy, R; Mondragón, E; Murphy, V (2008)
Using rules extracted from experience to solve problems in novel situations involves cognitions such as analogical reasoning and language learning and is considered a keystone of humans' unique abilities. Nonprimates, it has been argued, lack such rule transfer. We report that Rattus norvegicus can learn simple rules and apply them to new situations. Rats learned that sequences of stimuli consistent with a rule (such as XYX) were different from other sequences (such as XXY or YXX). When novel stimuli were used to construct sequences that did or did not obey the previously learned rule, rats transferred their learning. Therefore, rats, like humans, can transfer structural knowledge from sequential experiences.